Health centers in Rio Grande do Sul, Brazil: from implementation to consolidation, 1929-1943 - Ana Paula Korndörfer; Cristiano Enrique de Brum (História, Ciências, Saúde: Manguinhos, 2021)
Abstract The article analyzes the introduction, in the late 1920s, and consolidation, in the 1930s, of a public health model in Rio Grande do Sul state based on the health center model conceived in the United States. The genesis of health centers in the United States is discussed, as are two health reforms in Brazil, in 1929 and 1938, proposed by Fernando de Freitas e Castro and José Bonifácio Paranhos da Costa. The investigation draws not only on the literature in the area, but also on primary sources such as legislation, state health reports, and documents produced by the Rockefeller Foundation.